Comparing the Protagonistsâ Changes of Life Needs and the Fulfillments in `Cast Away` (2000) and `The Martian` (2015): A Psychological Study of Literature - Winarsih, Sri; Santoso, Heri Dwi; Mutmainnah, Yulia (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
In either literature or real life, oneâs motivation dealing with his/her satisfaction and need fulfillment in life can change as time goes by when experiencing some significant life transformation. Based on the above statement, this study was conducted. The material objects chosen were Cast Away (2000) and The Martian (2015), for there was some very similar formula in both movies in terms of plot, including the protagonistsâ phases of life, characteristics of setting and conflicts experienced by the protagonists related the studied topic. By applying Maslowâs theory of hierarchy of needs, the study was aimed at finding out the life needs of Chuck Noland, the protagonist in Cast Away, Mark Watney, the protagonistin The Martian including their changes and fulfillments within three different phases of life. The result showed that in both movies the protagonists experienced three different phases of life, which dealt significantly with what their ultimate life needs were within each phase and to what extent that the charactersâ were motivated to fulfill the needs. In the first phase, the protagonists tried to fulfill esteem need (4th level in hierarchy of needs). In the second phase, the characters pursued the fulfillment ofbelonging and love need (3th level in hierarchy of needs). And, in the third phase, both protagonists elevated the life standards due to fulfillment of (some of) the needs in previous phase. Chuck Noland in Cast Away had pursued love need but had not yet fulfilled belonging need (3th level in hierarchy of needs). Meanwhile Mark Watney in The Martian was already in process of fulfilling self-actualization (5th/top level in hierarchy of needs). It is concluded that when people experience some life transformations, regardless in better or worse situations that result in changes of life needs, they will try to adjust themselves to the new situations by trying to fulfill the new needs, neglecting the needs that they were pursuing in the previous situation.